Pengaruh Perencanaan Anggaran, Pelaksanaan Anggaran, Uang Persediaan, Dan Kompetensi Sumber Daya Manusia Terhadap Penyerapan Anggaran (Studi Pada Pengadilan Negeri Banjarmasin) - Mahfuzah, Rina Sari; Widyanti, Rahmi; Kurniaty, Kurniaty (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2024)
This research is motivated by the existence of activity planning not in accordance with needs because there is still an assumption that not all proposed budgets will be approved so that the proposed budget is greater than needed without paying attention to real needs in the field and ease of implementation, incomplete data supporting budget preparation so that the activity budget is blocked / asterisk. The activity budget is blocked, resulting in the budget cannot be disbursed until the block is unblocked. In addition to budget planning, budget implementation, and mature inventory money, human resource competence is also the cause of capital expenditure realization not being achieved, this is because the competence of human resources in preparing budgets is still low.This study aims to prove the factors that affect the level of budget absorption. The factors tested in this study are budget planning, budget implementation, Money Supply, and human resource competence.The population of this study was employees at the Banjarmasin District Court which amounted to 60 respondents. The total sample of this study was 60 respondents with a sampling technique, namely saturated samples. Data analysis was carried out using multiple linear regression processed with the help of SPSS program version 21.The results show that budget planning has a significant partial effect on budget absorption at the Banjarmasin District Court, budget implementation has a partial significant effect on budget absorption at the Banjarmasin District Court, supply money has a significant partial effect on budget absorption at the Banjarmasin District Court, Human resource competence has a significant partial effect on budget absorption at the Banjarmasin District Court, budget planning, budget implementation, supply money, and human resource competence have a significant simultaneous effect on budget absorption at the Banjarmasin District Court.